Model Project for Pancasila Students in Kindergarten - Dadan Suryana; Ayu, Ayu Mustika Sari; Farida Mayar; Nurbiana Dhieni; Sri Wulan (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
The research results show that children's development in kindergarten is still low because learning in kindergarten should emphasize children's active involvement in working on projects that are implemented in children's play activities. This research aims to develop the Pancasila Student Project model with the aim of improving children's development. This research uses development research (R&D), Plomp design and development. The objects in this research were 33 children. Data collection methods use observation, interviews and questionnaires. Instruments used in preliminary research, prototyping phase, and assessment phase of the Pancasila student model project to improve children's development. The technique used to analyze data is qualitative and quantitative descriptive analysis. The results of the research, namely the prototyping phase, obtained syntax, social systems, action principles, support systems, instructional impacts and accompanying project models to strengthen the profile of Pancasila students. The assessment phase of the validity test is (87), (91), and (93) criteria are very valid. The practicality test of observing the implementation of the learning model obtained an average of 87 model practicalities according to the teacher with very practical criteria. Based on this, the Pancasila Student Project model is suitable for use in learning.